Hairy root transgene expression analysis of a secretory peroxidase (PvPOX1) from common bean infected by Fusarium wilt. (July 2017) - Xue, Renfeng; Wu, Xingbo; Wang, Yingjie; Zhuang, Yan; Chen, Jian; Wu, Jing; Ge, Weide; Wang, Lanfen; Wang, Shumin; Blair, Matthew W.
Highlights: The expression profile of PvPOX1 indicated its defensive role in common beans infected by Fusarium wilt pathogen. PvPOX1 function was confirmed by the hairy root transformation mediated by Agrobacterium rhizogenes . The analysis of PvPOX1 overexpression hairy roots provided direct evidence for its role in the Fusarium wilt resistance. PvPOX1 gene was a valuable gene which can strengthen host defense response through a ROS activated resistance mechanism. Abstract: Plant peroxidases (POXs) are one of the most important redox enzymes in the defense responses. However, the large number of different plant POX genes makes it necessary to carefully confirm the function of each paralogous POX gene in specific tissues and disease interactions. Fusarium wilt is a devastating disease of common bean caused by Fusarium oxysporum f. sp. phaseoli . In this study, we evaluated a peroxidase gene, PvPOX1, from a resistant common bean genotype, CAAS260205 and provided direct evidence for PvPOX1 's role in resistance by transforming the resistant allele into a susceptible common bean genotype, BRB130, via hairy root transformation using Agrobacterium rhizogenes . Analysis of PvPOX1 gene over-expressing hairy roots showed it increased resistance to Fusarium wilt both in the roots and the rest of transgenic plants. Meanwhile, the PvPOX1 expressive level, the peroxidase activity and hydrogen peroxide (H2 O2 ) accumulation were also enhanced in the interaction. The result showed that the PvPOX1 gene played an essential role in Fusarium wilt resistance through the occurrence of reactive oxygen species (ROS) induced hypersensitive response. Therefore, PvPOX1 expression was proven to be a valuable gene for further analysis which can strengthen host defense response against Fusarium wilt through a ROS activated resistance mechanism.